Problems and Managerial Strategies in Arabic Language Learning: Senior High School Level - Muhammad Auli Rahman; Hakmi Wahyudi; Anugrah Ilahi; Izzatul Mellati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Arabic language learning in Madrasah Aliyah (MA) has a strategic position, both as a medium for understanding Islamic texts and as a means of developing students' communication skills. However, the implementation of Arabic language learning in MA still faces complex problems, ranging from curriculum aspects, teaching methods, availability of resources, to student motivation. This article aims to analyse the problems of Arabic language learning at the Madrasah Aliyah level and offer managerial solutions that can be applied by teachers, schools, and policymakers. This study uses a qualitative approach through field research. The results show that the main problems include low student interest in learning, limited teacher competence, the use of traditional methods, and limited learning media. The solutions offered include the application of innovative classroom management, the use of digital technology, continuous training for teachers, and the integration of real-life context-based learning. In conclusion, improving the quality of Arabic language learning in MA requires a comprehensive, collaborative, and student-oriented managerial approach. This article recommends integrative, collaborative, and student-centered learning management. With strong policy support, Arabic language learning can be more effective, enjoyable, and relevant in the era of globalization.